Mark : Paideia Commentaries on the New Testament - Beavis, Mary Ann. (Grand Rapids, MI : Baker Academic, 2011)
'In this addition to the well-received Paideia series, Mary Ann Beavis examines cultural context and theological meaning in Mark. Students, pastors, and other readers will appreciate the insights that Beavis derives from interrogating the text through multiple perspectives' -- Publisher description.
Mark 1:1-13 : Prologue : John and Jesus -- Mark 1:14-15 : Transition : Summary of the Good News -- Mark 1:16-3:35 : Act 1 : Jesus in Galilee -- Mark 4:1-34 : Interlude : Teaching in parables -- Mark 4:35-6:56 : Act 2 : Beyond Galilee -- Mark 7:1-23 : Interlude : Teaching on ritual and moral purity -- Mark 7:24-9:29 : Act 3 : Mission in Gentile regions -- Mark 9:30-10:52 : Interlude : Teaching on the way to Jerusalem -- Mark 11:1-12:44 : Act 4 : Opposition in Jerusalem -- Mark 13:1-37 : Interlude : Teaching on the End Times -- Mark 14:1-15:47 : Act 5 : Passion narrative -- Mark 16:1-8 : Epilogue : Women at the empty tomb.
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Mark Interpretation Commentary -- Mark Gospel Exposition Commentary